Glyoxal and methylglyoxal in Turkish commercial confectionery products - Mzoughi, Mondher; Yaman, Mustafa; Karimidastjerd, Atefeh; Vural, Ceyda; Catak, Jale; Toker, Omer Said (TAYLOR & FRANCIS LTD, 2026)
Glyoxal (GO) and methylglyoxal (MGO) are precursors of advanced glycation end products (AGEs). The objective of this study was to evaluate the content of GO and MGO in some Turkish confectionery products. A total of 20 samples were collected from markets and analysed for their GO and MGO content using high-performance liquid chromatography (HPLC). Results showed that GO content in the collected samples ranged from 4 +/- 1 & micro;g/100 g to 748 +/- 15 & micro;g/100 g, while the content of MGO varied between 9 +/- 1 & micro;g/100 g and 1205 +/- 74 & micro;g/100 g. Although some of the samples had relatively high levels of GO and MGO, these amounts remained within the range of GO and MGO content found in other Turkish food products reported in the literature. To minimise GO and MGO levels, measures such as optimising process conditions, modifying product ingredients, and monitoring these compounds after production should be implemented.
Keywords: Glyoxal; methylglyoxal; glycation products; confectionery; Chemistry; Food Science & Technology; Toxicology